Pengaruh Media Kartu Pantun terhadap Keterampilan Menulis Pantun Siswa Kelas V SD Negeri Sidodadi Kecamatan Kejuruan Muda - Rizky, Ridho; Nasution, Sahkolid; Syaifullah, Muhammad (Universitas Muhammadiyah Enrekang, 2024)
The aim of this research was to measure students' writing skills in both control and experimental classes before implementing learning using katu pantun media in class V of Sidodadi State Elementary School. This research also found that pantun cotton media can improve students' pantun writing skills. This research is a quantitative type of experimental research. This research involved 50 students from class V of Sidodadi State Elementary School, Youth Vocational District, which consisted of 2 classes: experimental class (IV-B) and control class (IV-A), each with 25 students each. A written test consisting of seven questions is used to measure students' abilities in pantun material. The software used to carry out data analysis and statistical tests is SPSS 27.0. The results of the research show that the rhyme writing skills of Sidodadi State Elementary School are greatly influenced by the presence of rhyme card media. The results of the hypothesis test also show that the experimental class treatment has an influence, because the sig. (2-fail) experimental class 0.000 is less than 0.05, so Ha and Ho are accepted at the level α = 0.05. For future research, this research must be supplemented with in-depth research on other topics that were previously researched.